Domestic water use in a rural village in Minas Gerais, Brazil, with an emphasis on spatial patterns, sharing of water, and factors in water use - Andréa Gazzinelli; Márcia Christina C. Souza; Iara Nascimento; Ilcéia Ribeiro Sá; Matilde Meire Miranda Cadete; Helmut Kloos
This paper examines the relationship between domestic water use and socioeconomic, environmental, and spatial parameters at the household level in a small rural village in northern Minas Gerais State. Five methods are used direct observation, household interviews, self-reporting by households, regression analysis, and statistical mapping. Results show that water use is characterized by 1) generally low but widely fluctuating values per person per day, 2) sharing of water sources between households, 3) the use of multiple sources by individual households, 4) avoidance of heavily contaminated stream sites, and 5) predominance of socioeconomic factors in water use. Households owning their own water supply used, on average, 25.3 liters per person/day and those without a supply 9.0 l, with higher use of the local streams among the latter. Water use varied spatially. The socioeconomic factors house quality, latrine ownership, type of water source, and a utility index were significantly correlated with water use. Implications of these simple household water sources and the more deficient sanitary facilities for potential water-borne disease transmission are briefly discussed and suggestions made for further improvements. This study confirms the appropriateness of the application of direct observation, interview, and microgeographical methods for quantitative water use studies.